Pengaruh Financial Distress, Capital Intensity, dan Komisaris Independen Terhadap Tax Avoidance pada Perusahaan Manufaktur Sektor Industri Barang dan Konsumsi yang Terdaftar di BEI Tahun 2020-2023 - Tantri, Virginia Amaylia; Yoshida, Debbie (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the effect of financial distress, capital intensity, and independent commissioners on tax avoidance. The population studied includes manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The sample used consists of 30 companies with a total of 120 observations over four years, using the purposive sampling method. This research applies a quantitative research method using secondary data obtained from the official website of the Indonesia Stock Exchange and the respective company websites. The analytical technique used in this study is multiple linear regression, processed using SPSS 25 software. The results of this study indicate that: (1) Financial Distress has a positive effect on Tax Avoidance, (2) Capital Intensity has a positive effect on Tax Avoidance, and (3) Independent Commissioners have no effect on Tax Avoidance.